PENGARUH PENGGUNAAN METODE DEMONSTRASI TERHADAP HASIL BELAJAR FISIKA SISWA MATERI POKOK USAHA DAN ENERGI KELAS VIII SMPN NEGERI 1 SIPIROK - Siregar, Dwi Aninditya (Jurnal Physics Education (PhysEdu), 2023)
The aim of this research was to know whether there is significant influence of using demonstration method on students’ achievement in work and energy subject at the eighth grade students of SMP Negeri 1 Sipirok. The population of this research was all the eighth grade students of SMP Negeri 1 Sipirok which include 7 classes. They were 225 students. Sample was teken by using cluster random sampling technique. So the total sample 40 students. The research used demonstration method. In collecting the data, the writer used test and questionnaire. The data was analyzed two ways. They were descriptive analysis and inferential statistic. The mean of using demonstration method in work and energy was 2.86. It was categorized “good”. The meanof students’ achievement in work and energy was 76.47, it is categorized “good”. Based on inferential statistic analisys, tcount is 4.,89 while ttable = 2.05, on 5% degree of freedom, df = N-nr = 40-2 = 38. It can be seen that tcount is greater than ttable (4.89> 2.05). the hypothesis is accepted. In another words, there is a significant influence between using demonstration method on students’ achievement in work and energy of the eighth grade students of SMP Negeri 1 Sipirok.